Penerapan Model Inkuiri Terbimbing Berbantuan Media Youtube Terhadap Hasil Belajar Siswa SMP - Parno Sumanro Mahulae; Jeanne Vera Tumangkeng; Kristiani Della Kaldera; Mutiara Syalomitha Sondakh (Gravity Journal, 2026)
This research is motivated by the low understanding of students at SMP Negeri 4 Tondano regarding Simple Machines material. This occurs because the learning process is still teacher-centered and the use of visual media that can help students understand concepts concretely is minimal. In fact, most students are already accustomed to using YouTube as a learning resource, but its utilization in physics learning has not been optimal. This study aims to determine the effectiveness of the Guided Inquiry model combined with YouTube media in improving students' learning outcomes on the Simple Machines material. The research uses a quantitative approach with a quasi-experiment method and a One Group Pretest-Posttest design. The research sample consists of 28 eighth-grade students selected using a random sampling technique. The research instrument was a multi The research results showed a significant increase in the students' average scores, from 37.64 in the pretest to 79.64 in the posttest. Analysis using N-Gain produced a score of 0.65, which falls into the medium category. Thirteen students were in the high category, 13 students in the medium category, and 2 students in the low category. These findings indicate that the Guided Inquiry model assisted by YouTube media is effective in improving conceptual understanding and supporting physics learning based on the Merdeka Curriculum.